Perancangan Website Penjualan Warung Nasi Bu Misyani Seikambing Medan Menggunakan Metode Prototype - Mayang Sari Nasution; Furqan Khalidy; Saiful Amir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The rapid advancement of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt web-based systems to improve sales performance and operational efficiency. However, Warung Nasi Bu Misyani Seikambing Medan still relies on manual sales processes, resulting in transaction recording errors, delays in sales reporting, and limited promotional activities. This study aims to design and develop a sales website that supports transaction management, promotional activities, and information delivery more effectively. The research employed the Research and Development (R&D) method using the Prototype development model. Data were collected through interviews, observations, and literature review, while system functionality was evaluated using Black Box Testing. The results indicate that the developed website provides integrated features, including menu management, sales transactions, sales reports, business information, online ordering without user registration, and both cash and QRIS payment options. System testing confirmed that all features functioned properly according to user requirements. Therefore, the developed website serves as an effective solution for improving sales management, accelerating customer service, expanding promotional reach, and supporting the operational efficiency of Warung Nasi Bu Misyani Seikambing Medan.